Oil Prices and Stock Market Returns in Oil Exporting Countries: Evidence from Saudi Arabia - Khamis, Reem; Anasweh, Mohammad; Hamdan, Allam (International Journal of Energy Economics and Policy, 2018)
This study aims at investigating the reaction of Saudi Arabia stock market towards oil price fluctuations a sectoral level in particular. The study covered 4 years from (2012-2015). This time series witnessed historical high and low oil prices. The results of the study added a new evidence for the asymmetric reaction of stock markets towards oil prices that was reported by previous studies. The study used Granger causality and regression tests to explore the dynamics of sectoral responses. Saudi Arabia stock market proved that they faced the current oil drops bravely although certain sectors need to unbind or reduce their relation with oil markets to reduce the consequences of low oil prices on them. Several avenues for future studies are opened to investigate all GCC stock markets and use other methodologies to better understand the dynamics of GCC market sectors towards oil prices fluctuations. Keywords: Saudi Arabia stock market; oil prices; granger causality. JEL Classifications: E44, Q21